2015
DOI: 10.1016/j.ecoser.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Mapping ecosystem service flows with land cover scoring maps for data-scarce regions

Abstract: a b s t r a c tNatural resource management requires spatially explicit tools to assess the current state of landscapes, to analyse trends and to develop suitable management strategies and interventions. The concept of ecosystem services can help in understanding the importance of natural resources for different stakeholders and at different spatial and temporal scales. Simple methods to map ecosystem services using scoring of land cover types are particularly useful in data scarce regions, but do not reflect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 54 publications
0
50
0
1
Order By: Relevance
“…land cover maps and global or national databases) rather than field data. Using secondary data requires substantial amounts of available input data, which seldom exist in poor and marginalized areas where people depend heavily on ecosystems for their livelihoods (Ramirez-Gomez et al, 2015;Vrebos et al, 2014). Most mapping studies of ecosystem services have been done on large spatial scales (regional, provincial, and national), with only a very few studies comparable to the size of a village (Malinga et al, 2015;Martínez-Harms and Balvanera, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…land cover maps and global or national databases) rather than field data. Using secondary data requires substantial amounts of available input data, which seldom exist in poor and marginalized areas where people depend heavily on ecosystems for their livelihoods (Ramirez-Gomez et al, 2015;Vrebos et al, 2014). Most mapping studies of ecosystem services have been done on large spatial scales (regional, provincial, and national), with only a very few studies comparable to the size of a village (Malinga et al, 2015;Martínez-Harms and Balvanera, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…in soil carbon storage, biodiversity and pollination). This reflects the multifunctional role of semi-natural habitats in ES delivery, as reported in other studies (Burkhard et al 2012;Vrebos et al 2015;Crouzat et al 2015;and Lamy et al 2016). In contrast, intensively managed habitat types such as coniferous wood or arable land are more homogenous, have less habitat diversity and hence have lower capacities to supply multiple ESs (Burkhard et al 2012).…”
Section: Discussionmentioning
confidence: 64%
“…The fact that maps cannot provide definitive evidence of interrelationships is one reason for the generalised nature of the findings reported in this paper. In addition, means for assessing map accuracy and validation of maps remain insufficiently addressed in many current ES mapping practices (Schulp et al 2014;Willemen et al 2015), although different modes of stakeholder consultation are now being explored to address such shortcomings (Vrebos et al 2015). In this study, the 2009 ES maps produced for the Scottish Borders regional land-use pilot project were validated by the local stakeholders and also led to certain refinements of the ES maps.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of using soil information directly, some of the mapping and modeling exercises used environmental variables as a proxy to soil information (Deng et al, 2011;Egoh et al, 2008;Guerra et al, 2014;Sumarga and Hein, 2014;e.g., Trabucchi et al, 2014). The most commonly used proxy is the land use and land cover (LULC) data (Plieninger et al, 2013;Schägner et al, 2013;Seppelt et al, 2011) which have been found useful in regions where data are scarce (Vrebos et al, 2015). LULC data are often favored to produce spatially distributed biophysical parameter values needed for production function models, e.g., many of the InVEST models (Kareiva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%